Linear IgA disease responsive to monotherapy with dapsone. Case report. - Vitiello, P.; Auricchio, L.; Mezza, E.; Mansueto, G.; Stasio, L.; Limongelli, M.G.; Franzese, A.; Pennacchia, W. (European Journal of Pediatric Dermatology, 2006)
A three year old girl presented with pneumonia and a sudden erythematous and bullous eruption suggestive of linear IgA disease. Clinical diagnosis was confirmed by direct immunofluorescence on skin biopsy fixed in formaldehyde and embedded in paraffin. The patient recovered after therapy with dapsone 1.6 mg/kg per day.